Association of Gamma-GT Serum and Nerve Conduction Velocity of Nervus Peroneus Motor Vehicles on Diabetic Polyneuropathy Patients - Januar1 , Mudjiani Basuki2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Objectives: Diabetic Polyneuropathy is one of the common complications of diabetesmellitus (DM) and can lead to foot ulcers or amputation. The pathophysiology of Diabetic Polyneuropathyincludes several factors such as metabolic, vascular, autoimmune, oxidative stress and neurohormonalgrowth-factor deficiency. The recent studies have suggested the use of serum gammaglutamyl transferase(GGT) as an early marker of oxidative stress. Therefore, we investigated whether serum GGT may be usefulin predicting Diabetic Polyneuropathy.Methods: The study was conducted in patients with diabetic polyneuropathy who meet the criteria forinclusion and exclusion in neurological outpatient clinic and EMG room departments of NeurologyDr.Soetomo General Hospital Surabaya consecutively started in June 2014 to April 2015.Result: We obtained 20 study subjects (8 subjects with increased serum levels of gamma GT and 12 subjectswith normal serum levels of gamma GT). There was statistically no significant between serum levels ofgamma GT with motoric nerve conduction velocity (NCV) of peroneal nerve (p = 0.582 ; Odds ratio 0.600).Conclusion: There was no relationship between elevated levels of serum gamma GT with decreased motornerve conductivity velocity peroneal nerve in patients with diabetic polyneuropathy.